Mental health literacy and help-seeking: the mediating role of self-stigma and emotional intelligence - Awan, Mahd; Boyce, Melissa A.; Lindsay, Brittany L. (Frontiers in Psychology, 2025)
When faced with mental health concerns, help-seeking can be a useful means to seek and receive help from formal support sources—such as mental health professionals, as well as informal support sources—such as friends and family. Both the intention and tendency to engage in formal help-seeking are predicted by mental health literacy, self-stigma, and emotional intelligence; however, the role that each of these factors play in relation to informal help-seeking is less clear. The current study examined the predictive value of mental health literacy with respect to both formal and informal help-seeking intentions. Additionally, the current study explored the role of self-stigma and emotional intelligence as possible mediators of these relationships. Undergraduate students (n = 301) were recruited from a Western Canadian university and completed a series of online questionnaires measuring their formal and informal help-seeking intentions, mental health literacy, self-stigma faced when seeking help, and meta-mood, as an operationalization of emotional intelligence. Results indicated that mental health literacy was a significant positive predictor of formal help-seeking intentions, and that both self-stigma and meta-mood partially mediated this relationship. Furthermore, results showed that mental health literacy did not serve as a significant predictor of informal help-seeking, although mental health literacy did have a significant indirect effect on informal help-seeking, through the mediation of meta-mood. The importance of self-stigma and meta-mood in relation to mental health literacy are highlighted in terms of formal help-seeking outcomes, and the implications of these findings for informal help-seeking are discussed.